Technology Entrepreneurship (ENT 600) : Klean Kanteen / Nor Iwani Farzana Mohamad Zamri - Mohamad Zamri, Nor Iwani Farzana (2021)
This is an attempt to know how the theories can be applied to practical situation. As a student in UiTM Arau, Perlis, it is a part of study for everyone to undergo a case study project. So for this purposed, I got the opportunity to do research on a company which manufactured the same product that I want to develop in new product development(NPD). the company that I have been chosen is Klean Kanteen that produce thermos and many type of reusable water bottle. The general information of the company has been collected. The information that I get is through the searching in the internet. This is due to Pandemic Covid 19(MCO) in Malaysia that limit the activities of each student. I also analysis the strength, weakness, opportunities and threats of company by using SWOT analysis. The solution that I gain will be later use on the develop in new product development(NPD).